5 - The Gendered and Commodified Female Body in Contemporary Nigerian Fiction - Egya, Sule Emmanuel (Africa Development, 2018)
Although African feminist scholarship has grown diverse and dynamic over the years, it seems that little attention is paid to the discursive corporeality of the female body. It is often implied that discourses about the fate of the woman under a patriarchal system already caters for the body of the woman. There is however the need to stage or foreground the female body, by way of giving it much closer attention, its discursive formation, its use and abuse, its process of inscription, and its genderisation as it often fails to escape the exertions of patriarchy. Reading three contemporary Nigerian novels: Zaynab Alkali’s The Descendants, Unoma Azuah’s Sky-High Flames, and Lola Shoneyin’s The Secret Lives of Baba Segi’s Wives, this article examines the representation of the female body in fictional narratives with specific focus on how the body is gendered, sexualized and commodified. The article argues that in the process of inscribing gender and sexuality on the body and commodifying it, the question of body aesthetics is thrown up – the ironic privileging of the beautiful body, the place of the ugly body, the implications of the deformed body, and the entire artificial way of making the body what it is not. The article, after an analysis of the gendered and commodified female body in the novels mentioned above, concludes that the body is a victim of patriarchal and institutional power that inscribes positions and prejudices on it and gestures it towards what one may call self-inferioritisation, although the novelists offer hope of self-emancipation.